Thermodynamic and viscous behaviour of glass forming melts and glass forming ability - Dubey K.S. (My University, 2025)
The bulk metallic glasses (BMGs) have achieved a great interest due to their scientific and potential technological applications and these are among the most extensively studied advanced materials. The understanding of the glass forming ability (GFA) of these multicomponent metallic alloys is an essential parameter to develop new non-crystalline materials which is an outstanding problem for being adequately solved. The Gibbs free energy difference (ΔG) between the undercooled melt and the corresponding equilibrium solid phases and the viscosity (η) of the undercooled melts are essential parameters for understanding the nucleation and growth processes. The present article deals with the procedures for obtaining the expressions for ΔG as well as the expressions for obtaining the temperature dependence of viscosity of the undercooled melts. The method for evaluation of the Kauzmann temperature T k and its importance has also been discussed. The glass forming ability (GFA) of materials is explained in terms of ratio of specific heat difference ΔCpm and entropy difference ΔS m at the melting temperature Tm. The role of various thermodynamic quantities in GFA of materials has also been discussed. The discussion is confined to simple, oxide, polymeric and bulk metallic glasses. © 2010 American Institute of Physics.